2020
DOI: 10.1186/s12904-020-00624-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the costs, consequences and efficiency of three types of palliative care day services in the UK: a pragmatic before-and-after descriptive cohort study

Abstract: Background: Palliative Care Day Services (PCDS) offer supportive care to people with advanced, progressive illness who may be approaching the end of life. Despite the growth of PCDS in recent years, evidence of their costs and effects is scarce. It is important to establish the value of such services so that health and care decision-makers can make evidence-based resource allocation decisions. This study examines and estimates the costs and effects of PCDS with different service configurations in three centres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…For instance, in one hospice, day therapies were part of the overall community nursing service, whereas in others day therapies was a separate service. The interventions offered within day therapies also varied as has been described elsewhere [8].…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in one hospice, day therapies were part of the overall community nursing service, whereas in others day therapies was a separate service. The interventions offered within day therapies also varied as has been described elsewhere [8].…”
Section: Settingmentioning
confidence: 99%
“…Hospices are evolving and have shifted their focus from caring for patients with cancer to the development of services for all terminally ill patients; while also seeking to offer services earlier in the illness trajectory when needed. As hospice services have developed to suit the needs of their local population and receive only partial statutory funding through local commissioning processes, there is much variability in the services offered [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of costs in three palliative day care services in the UK (2020) found that the contributions of volunteers (as complementary therapists, drivers, catering staff or hairdressing) was equivalent to roughly a third (28-38%) of running costs per day per patient. [ 58 ] The hospice sector depends upon volunteers, and thus community engagement that increases the visibility of hospice volunteering could be considered essential to workforce planning.…”
Section: Discussionmentioning
confidence: 99%
“…Data were collated from two studies conducted within the same setting, one a before-and-after cohort study examining the costs and outcomes of the use of palliative care day services (PCDS) [15] and the other exploring the use of an educational intervention for staff designed to improve the management of constipation in hospice patients [16,17]. Both recruited from a national chain of hospices in the UK.…”
Section: Samplementioning
confidence: 99%
“…As this was the first use of the ICECAP-SCM, there were no available data to perform a sample size calculation. In addition, the research question on the validity of the ICECAP-SCM in hospice care was not the main focus of the studies where this data was collected, with sample size being driven by their primary research questions [15][16][17].…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%